High‐Throughput Computational Characterization of 2D Compositionally Complex Transition‐Metal Chalcogenide Alloys. Issue 11 (7th October 2020) - Wang, Duo; Liu, Lei; Basu, Neha; Zhuang, Houlong L.
Abstract: 2D binary transition‐metal chalcogenides (TMCs) such as molybdenum disulfide exhibit excellent properties required for energy conversion applications. Alloying binary TMCs can form 2D compositionally complex TMC alloys (CCTMCAs) that possess remarkable properties from the constituent TMCs. High‐throughput workflow performing density functional theory (DFT) calculations based on the virtual crystal approximation (VCA) model (VCA‐DFT) is designed. The workflow is tested by predicting properties including in‐plane lattice constants, band gaps, effective masses, spin–orbit coupling, and band alignments of the Mo‐W‐S‐Se, Mo‐W‐S‐Te, and Mo‐W‐Se‐Te 2D CCTMCAs. The VCA‐DFT results are validated by computing the same properties using unit cells and supercells of selected compositions. The VCA‐DFT results of the abovementioned five properties are comparable to that of DFT calculations, with some inaccuracies in several properties of MoSTe and WSTe. Moreover, 2D CCTMCAs can form type II heterostructures as used in photovoltaics. Finally, Mo0.5 W0.5 SSe, Mo0.5 W0.5 STe, and Mo0.5 W0.5 SeTe 2D CCTMCAs are used to demonstrate the room‐temperature entropy‐stabilized alloys. They also exhibit high electrical conductivities at 300 K, promising for light adsorption devices. This work shows that the high‐throughput workflow using VCA‐DFT calculations provides a tradeoff between efficiency and accuracy, opening up opportunities in the computational design of other 2D CCTMCAs for various applications. Abstract : A high‐throughput workflow using density functional theory calculations based on the virtual crystal approximation is designed to simulate over 1300 2D compositionally complex transition‐metal chalcogenides (CCTMCAs). Many of these 2D CCTMCAs, especially those with high configurational entropy, are found to exhibit promising energy‐related applications. This workflow also opens up ample opportunities in the discovery of other 2D CCTMCAs.